2022
DOI: 10.1136/postgradmedj-2021-140540
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells and serum immunoglobulins are associated with disease severity and mortality in patients with COVID-19

Abstract: Purpose of the studyThe aim of this study was to investigate the relationship of B cell-mediated immunity with disease severity and mortality in patients with COVID-19.Study designIn this retrospective cohort and single-centre study, 208 patients with laboratory-confirmed COVID-19 were recruited. A COVID-19 severity score, ranging from 0 to 10, was used to evaluate associations between various factors. Serum immunoglobulin levels and the number of cells in B lymphocyte subsets were measured and their associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Severe COVID-19 patients showed extrafollicular B cells activation with expansion of PBs that inevitably produce high titers of antibodies, similarly to what was reported in autoimmune diseases, which strongly correlates with the level of proinflammatory cytokines (96,113). The lack of a positive correlation between the titer of neutralizing antibodies and disease severity has been shown by several reports (114,115), though others have found reduced levels of SARS-CoV-2-specific peripheral IgA, IgG, and IgG1 in severe/critical COVID-19 patients (116). In particular, such populations are characterized by CD19 + CD27 + CD38 hi antibody-producing cells, as well as CD11 + activated naïve B cells that differentiate in effector B cells lacking naïve (IgD) and memory (CD27) markers, i.e.…”
Section: Antigen-specific B Cell and Humoral Responsessupporting
confidence: 73%
See 1 more Smart Citation
“…Severe COVID-19 patients showed extrafollicular B cells activation with expansion of PBs that inevitably produce high titers of antibodies, similarly to what was reported in autoimmune diseases, which strongly correlates with the level of proinflammatory cytokines (96,113). The lack of a positive correlation between the titer of neutralizing antibodies and disease severity has been shown by several reports (114,115), though others have found reduced levels of SARS-CoV-2-specific peripheral IgA, IgG, and IgG1 in severe/critical COVID-19 patients (116). In particular, such populations are characterized by CD19 + CD27 + CD38 hi antibody-producing cells, as well as CD11 + activated naïve B cells that differentiate in effector B cells lacking naïve (IgD) and memory (CD27) markers, i.e.…”
Section: Antigen-specific B Cell and Humoral Responsessupporting
confidence: 73%
“…The expansion of B cells lacking memory markers has been described in several studies and has been referred to as atypical memory B cells (CD21 lo CD27 -CD10 -) (118). Additionally, a decrease of switched memory B cells was suggested as independent risk factor for mortality in COVID-19 patients (116), whereas proliferating memory B cells were not associated with severity (96). Importantly, the antibody-secreting cells produce high levels of antibodies that can have neutralizing features in severe COVID-19 patients, as shown in several studies (63,119,120).…”
Section: Antigen-specific B Cell and Humoral Responsesmentioning
confidence: 99%
“…Since memory B cells and serum immunoglobulins are associated with disease severity and mortality in patients with COVID-19, it is essential to examine what happens when this humoral part of the immune response is impaired. To be more precise, more severe disease and deceased patients have significantly lower levels of total B cells, naive B cells, switched memory B cells, and serum IgA, IgG, IgG1, and IgG2 than recovered patients ( 42 ). Furthermore, the persistence of neutralizing antibodies was associated with greater disease severity ( 43 ).…”
Section: T Cell Immunity Existence Despite Impaired Humoral Response ...mentioning
confidence: 99%
“…al. found that a lower number of B cells was associated with severe disease and was linked to poor outcomes in COVID-19 patients [23] . SARS-CoV-2 infection has also been proposed to affect both the number of circulating NK cells and their phenotype, leading to impairment, exhaustion and hyporesponsiveness.…”
Section: Discussionmentioning
confidence: 96%